Organisasi Kepemimpinan dan Manajemen Personalia - Angwarmase, Raimondus (LaKaspia, 2023)
This study aims to analyze the relationship between organization, leadership, and personnel management in enhancing organizational performance. The focus of this research is to understand how leadership styles and personnel management strategies contribute to organizational effectiveness and efficiency. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document studies in several organizations in both the public and private sectors. The results of the study indicate that transformational and participative leadership styles have a significantly positive impact on employee motivation and performance, while effective personnel management, particularly in recruitment, training, and development, plays a key role in improving employee retention and satisfaction. The conclusion of this study is that synergy between effective leadership and structured personnel management can enhance overall organizational performance. This research suggests the need for the implementation of more adaptive and flexible personnel management strategies and the development of leadership that is responsive to changes in the organizational environment Abstrak Penelitian ini bertujuan untuk menganalisis hubungan antara organisasi, kepemimpinan, dan manajemen personalia dalam meningkatkan kinerja organisasi. Fokus penelitian ini adalah memahami bagaimana gaya kepemimpinan dan strategi manajemen personalia berkontribusi terhadap efektivitas dan efisiensi organisasi. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi pada beberapa organisasi di sektor publik dan swasta. Hasil penelitian menunjukkan bahwa gaya kepemimpinan yang transformasional dan partisipatif memiliki pengaruh positif yang signifikan terhadap motivasi dan kinerja karyawan, sementara manajemen personalia yang efektif, terutama dalam hal perekrutan, pelatihan, dan pengembangan, memainkan peran kunci dalam meningkatkan retensi dan kepuasan karyawan. Kesimpulan dari penelitian ini adalah bahwa sinergi antara kepemimpinan yang efektif dan manajemen personalia yang terstruktur dapat meningkatkan kinerja organisasi secara keseluruhan. Penelitian ini menyarankan perlunya penerapan strategi manajemen personalia yang lebih adaptif dan fleksibel serta pengembangan kepemimpinan yang responsif terhadap perubahan lingkungan organisasi